High Rates of Hepatitis C Virus Reinfection and Spontaneous Clearance of Reinfection in People Who Inject Drugs: A Prospective Cohort Study - Sacks-Davis, R.; Aitken, C.; Higgs, Peter; Spelman, T.; Pedrana, A.; Bowden, S.; Bharadwaj, M.; Nivarthi, U.; Suppiah, V.; George, J.; Grebely, J.; Drummer, H.; et al. (Public Library of Science, 2013)
Hepatitis C virus reinfection and spontaneous clearance of reinfection were examined in a highly characterisedcohort of 188 people who inject drugs over a five-year period. Nine confirmed reinfections and 17 possiblereinfections were identified (confirmed reinfections were those genetically distinct from the previous infection andpossible reinfections were used to define instances where genetic differences between infections could not beassessed due to lack of availability of hepatitis C virus sequence data). The incidence of confirmed reinfection was28.8 per 100 person-years (PY), 95%CI: 15.0-55.4; the combined incidence of confirmed and possible reinfectionwas 24.6 per 100 PY (95%CI: 16.8-36.1). The hazard of hepatitis C reinfection was approximately double that ofprimary hepatitis C infection; it did not reach statistical significance in confirmed reinfections alone (hazard ratio [HR]:2.45, 95%CI: 0.87-6.86, p=0.089), but did in confirmed and possible hepatitis C reinfections combined (HR: 1.93,95%CI: 1.01-3.69, p=0.047) and after adjustment for the number of recent injecting partners and duration of injecting.In multivariable analysis, shorter duration of injection (HR: 0.91; 95%CI: 0.83-0.98; p=0.019) and multiple recentinjecting partners (HR: 3.12; 95%CI: 1.08-9.00, p=0.035) were independent predictors of possible and confirmedreinfection. Time to spontaneous clearance was shorter in confirmed reinfection (HR: 5.34, 95%CI: 1.67-17.03,p=0.005) and confirmed and possible reinfection (HR: 3.10, 95%CI: 1.10-8.76, p-value=0.033) than primary infection.Nonetheless, 50% of confirmed reinfections and 41% of confirmed or possible reinfections did not spontaneouslyclear.Conclusions: Hepatitis C reinfection and spontaneous clearance of hepatitis C reinfection were observed at highrates, suggesting partial acquired natural immunity to hepatitis C virus. Public health campaigns about the risks ofhepatitis C reinfection are required.